The Greek-Turkish Bilateral Relations Revised: Towards an Era of ‘Conflictual Cooperation’? - Koukakis, Georgios (HAPSc Policy Briefs Series, 2024)
The contemporary bilateral relations of Greece and Turkiye have been mostly characterised by tension, as they have led in several occasions to major diplomatic incidents and military crises. In 2017 a rapprochement in the form of regular high-level political meetings was initiated, only to be terminated in mid-2022 when the Turkish President stated that the Greek Prime Minister no longer existed for him terminating the established political dialogue, due to the latter’s address to the Joint Session of the US Congress. The support though that Greece provided to Turkiye in early-2023, after the devastating earthquake that stroke the latter, significantly improved the relations of the two sides leading in late-2023 to the signature of the ‘Athens Declaration’ and an several accords regarding their cooperation in various policy fields, acknowledging though the fact that their main issues of dispute remain active. The purpose of this article is to highlight the new dynamics of the Greek-Turkish relations in the context of their ongoing dispute.